EUS-FNA Biopsies to Guide Precision Medicine in Pancreatic Cancer: Results of a Pilot Study to Identify KRAS Wild-Type Tumours for Targeted Therapy - Lundy, Joanne; Harris, Marion; Zalcberg, John; Zimet, Allan; Goldstein, David; Gebski, Val; Borsaru, Adina; Desmond, Christopher; Swan, Michael; Jenkins, Brendan J.; Croagh, Daniel (Frontiers in Oncology, 2021)
Background: Pancreatic ductal adenocarcinoma (PDAC) is a leading cause of cancer death and lacks effective treatment options. Diagnostic endoscopic ultrasound-guided fine-needle aspiration (EUS-FNA) biopsies represent an appealing source of material for molecular analysis to inform targeted therapy, as they are often the only available tissue for patients presenting with PDAC irrespective of disease stage. However, EUS-FNA biopsies are typically not used to screen for precision medicine studies due to concerns about low tissue yield and quality. Epidermal growth factor receptor (EGFR) inhibition has shown promise in clinical trials of unselected patients with advanced pancreatic cancer, but has not been prospectively tested in KRAS wild-type patients. Here, we examine the clinical utility of EUS-FNA biopsies for molecular screening of KRAS wild-type PDAC patients for targeted anti-EGFR therapy to assess the feasibility of this approach. Patients and methods: Fresh frozen EUS-FNA or surgical biopsies from PDAC patient tumours were used to screen for KRAS mutations. Eligible patients with recurrent, locally advanced, or metastatic KRAS wild-type status who had received at least one prior line of chemotherapy were enrolled in a pilot study (ACTRN12617000540314) and treated with panitumumab at 6mg/kg intravenously every 2 weeks until progression or unacceptable toxicity. The primary endpoint was 4-month progression-free survival (PFS). Results: 275 patient biopsies were screened for KRAS mutations, which were detected in 88.3% of patient samples. 8 eligible KRAS wild-type patients were enrolled onto the interventional study between November 2017 and December 2020 and treated with panitumumab. 4-month PFS was 14.3% with no objective tumour responses observed. The only grade 3/4 treatment related toxicity observed was hypomagnesaemia. Conclusions: This study demonstrates proof-of-principle feasibility to molecularly screen patients with pancreatic cancer for targeted therapies, and confirms diagnostic EUS-FNA biopsies as a reliable source of tumour material for molecular analysis. Single agent panitumumab was safe and tolerable but led to no objective tumour responses in this population.